(untitled) (Journal of Science and Technology, 2016)
Using the fast Fourier transform (FFT) method, we determined the spectral characteristics of some meteorological variables over Kenya and identified the prominent periodicities associated with the variables. The meteorological variables studied are the maximum temperature, mini- mum temperature, average temperature, wind speed, precipitation, relative humidity, solar radia- tion intensity, evaporation and sunshine duration. Data from five terrestrial stations, represent- ing the regional climatic zones in Kenya, were employed in the study. The result reveals periods that are associated with solar activity. It is established that solar forcing is very significant over the Kenyan climate. The Sun-Climate relations were influenced at some locations by local ef- fects such as orography and vegetation.